ANALISIS PENDAPATAN USAHATANI TOMAT DI DESA TARAITAK SATU KECAMATAN LANGOWAN UTARA (Income Analysis of Tomato Farming in Taraitak Satu Village of North Langowan District) - Putri Rhizka Amalia Bongkang; Paulus A. Pangemanan; Ellen G. Tangkere (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2019)
The purpose of this study was to analyze the income of tomato farming in Taraitak Satu Village, North Langowan District. This research was conducted for three months from March 2019 to May 2019. The data used in this study were primary data obtained based on interviews with 20 respondents of tomato farmers who were taken by simple random sampling and secondary data obtained from the village office and sub-district offices and literature available in libraries and the internet related to research.Research results show that the average income of tomato farming was Rp. 34,227,279 / planting season with an average of seven harvest seasons. The total revenues was Rp. 47,976,000 with a total cost of Rp. 13,748,721.To obtain a better sale price, farmers are advised to set the planting time so that it is not done simultaneously. In addition, farmers can expand their markets, for example, by selling to supermarkets or outside the region in order to obtain better profits in tomato farming. Keywords: Tomato Farm, Â Income Analysis